DEVELOPING AND PRACTICING INCLUSIVE LEADERSHIP IN SCHOOLS - Murwanto, Petrus (PROGRES PENDIDIKAN, 2024)
This study aimed to investigate the concept of inclusive leadership, especially in the context of educational institutions that are becoming more diverse, and to explore how it can be developed and put into practice. The research methodology used was a literature review. The findings suggest that inclusive leadership is crucial in addressing issues related to equity, social justice, and diversity. It is also vital to create inclusive schools that welcome and celebrate diversity. The research concludes that by practicing inclusive leadership and highlighting the importance of culturally responsive leadership, educational leaders can help schools become places where all students are recognized, valued, and included in the educational process. Ultimately, this can lead to social justice through inclusion.